The text: meaning and (pre)construction between Self and Other (Signifiances (Signifying), 2022)
Language productions are always marked by déjà-là, norms and pre-constructs that are part of the inherent alterity of language, while meaning construction is difficult to achieve by simply reproducing this heritage, to which the speaker will in turn contribute. How are Self and Other articulated in this perspective of linguistic creativity aiming at producing a text, which is a unique object in itself? The study of the process of written textualisation brings to light the different ways to production, from writing for oneself in the incipient phases to writing for others, with an increasingly marked consideration of what the writer imagines to be the contextual constraints and the generic or social norms that enable him or her to respond to the image he or she has of the expectations of the recipients. Creativity, strictly speaking, is architectural, when the incremental dimension exploiting pre-constructions articulates the modular dimension anchored in the speaker’s experience.